Does Adlerian Play Therapy Increase Social, Physical, and Task Appeal More Than Content Mastery Services in Elementary School Students? - Bilqis, Fajar (Universitas Nahdlatul Ulama Surabaya, 2021)
This study examined the difference in effectiveness between Adlerian Play Therapy and content mastery services in increasing physical, social, and task attractiveness to students in primary schools. The factorial design experimental method was applied to 72 fifth-grade students from two public elementary schools in Bandung, Indonesia, whose dimensions of attractiveness were lower than the other study groups. Each intervention carried out six meetings in different schools. Adlerian Play Therapy starts from the one-session relationship-building stage, the lifestyle investigation stage through the three-session secret book, the lifestyle understanding stage through one-session games, and the reorientation & re-education stage through one-session games. Classical guidance services for content mastery with a community circle strategy start from building relationships in two sessions, introducing the importance of one session, improving the social aspects of one session, improving the physical aspects of one session, and improving the aspects of one session assignments. Manova analyzed the Interpersonal Attraction Scale (IAS) instrument. Adlerian Play Therapy further enhances all dimensions of interpersonal attractiveness than content mastery services. Recommendations are aimed at counseling teachers to use Adlerian Play Therapy to increase children's social, physical, and assignment attractiveness. It is hoped that other researchers will research further related to increasing task attractiveness.